EVALUATION OF CRUSTAL STRUCTURE AND BEDROCK TOPOGRAPHY AROUND MIZUHO PLATEAU, ANTARCTICA, BASED ON GRAVITY DATA - クドウ, タケシ; ナガオ, トシヤス; KUDO, Takeshi; NAGAO, Toshiyasu (National Institute of Polar Research, 1994)
P(論文) For the last three decades, gravity surveys around Syowa Station have been conducted by the Japanese Antarctic Research Expedition (JARE). Especially, in the vicinity of Mizuho Plateau, gravity data made it possible to analyze three-dimensional subsurface structures. The data have revealed several contradictions between gravity anomaly and ice thickness measured by radio echo sounding. To explain ice thickness data and gravity anomaly-bedrock height relations without any contradiction, about 5g/cm^3 of bedrock density is required. This high density is quite unnatural. In this study, the authors tried to construct the three-dimensional bedrock topography and shape of the Moho discontinuity by using gravity anomaly data. Through the analysis, we clarified the characteristics of the contradictions and found that ice thickness determined by radio echo soundings is always smaller than the actual thickness by a constant factor. Possible explanations are : 1) radio echo sounding detects an intra-ice discontinuity due to moraine and/or climatic change origin; 2) error of radio wave velocity due to variation of the estimated dielectric constant. This conclusion could explain theoretically the greatest part of the unnatural relationship between gravity anomaly and bedrock topography. departmental bulletin paper